2022
DOI: 10.3390/su14031898
|View full text |Cite
|
Sign up to set email alerts
|

Applying Machine Learning to Explore Feelings about Sharing the Road with Autonomous Vehicles as a Bicyclist or as a Pedestrian

Abstract: The current literature on public perceptions of autonomous vehicles focuses on potential users and the target market. However, autonomous vehicles need to operate in a mixed traffic condition, and it is essential to consider the perceptions of road users, especially vulnerable road users. This paper builds explicitly on the limitations of previous studies that did not include a wide range of road users, especially vulnerable road users who often receive less priority. Therefore, this paper considers the percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Tan et al (2019) [59] investigated choice behavior based on logistics models, considering participants' personal characteristics, travel demand, and cognitive aspects of autonomous vehicles. Another study by Asadi-Shekari et al (2022) [60] applied machine learning to explore emotions about sharing the road with autonomous vehicles as a cyclist or pedestrian. Azevedo et al (2016) [61] conducted a study focusing on the microsimulation of the supply and demand of autonomous mobility on demand.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…Tan et al (2019) [59] investigated choice behavior based on logistics models, considering participants' personal characteristics, travel demand, and cognitive aspects of autonomous vehicles. Another study by Asadi-Shekari et al (2022) [60] applied machine learning to explore emotions about sharing the road with autonomous vehicles as a cyclist or pedestrian. Azevedo et al (2016) [61] conducted a study focusing on the microsimulation of the supply and demand of autonomous mobility on demand.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…XGBoost has been widely used in various areas of transportation, such as traveler perception, traffic volume prediction, transportation safety, and risk analysis, and has achieved better results than traditional algorithms. Asadi-Shekari [36] introduced an algorithm based on XGBoost and analyzed the perceptions of vulnerable road users towards sharing the road with autonomous vehicles. The results showed that XGBoost is highly effective and accurate in predicting the views of cyclists or pedestrians.…”
Section: Introductionmentioning
confidence: 99%